Pengembangan E-Modul Berbasis Android Pada Mata Pelajaran Pemeliharaan Mesin Kendaraan Ringan - Diki Rezeki Yudiono (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to compile and test the feasibility of the fuel system E-module for class XI of the Automotive Light Vehicle Engineering Department at SMK Muhammadiyah Piyungan. This includes research and development with 4D models. The subjects in this study consisted of material experts and media experts as well as class XI students majoring in Automotive Light Vehicle Engineering at SMK Muhammadiya Piyungan as users of the learning media developed. The object of research is teaching materials. The technique of collecting data is using a questionnaire and observation. The data analysis technique used quantitative descriptive. The research instrument uses preliminary study instruments, expert validation instruments, and product testing instruments. The results of the research are: (1) The learning e-module product for Light Vehicle Engine Maintenance at SMK Muhammadiyah Piyungan was developed based on the 4D research model, namely: Define, Design, Develop and Disseminate, and (2) E-Module development is suitable for use as teaching materials. This is evidenced by the average score of the material expert validation results of 3.01 including the appropriate category, from the media expert getting a score of 3.00 including the appropriate category, from the field test results getting a score of 3.09 including the appropriate category, so that the overall average of the validation results by the material expert, media experts, and field tests get an average score of 3.03 including the appropriate category.